2020
DOI: 10.3390/nu12092764
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Worsens Gulf War Illness Symptom Persistence Pathology by Linking Altered Gut Microbiome Species to Long-Term Gastrointestinal, Hepatic, and Neuronal Inflammation in a Mouse Model

Abstract: Persistence of Gulf War illness (GWI) pathology among deployed veterans is a clinical challenge even after almost three decades. Recent studies show a higher prevalence of obesity and metabolic disturbances among Gulf War veterans primarily due to the existence of post-traumatic stress disorder (PTSD), chronic fatigue, sedentary lifestyle, and consumption of a high-carbohydrate/high-fat diet. We test the hypothesis that obesity from a Western-style diet alters host gut microbial species and worsens gastrointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 69 publications
4
43
0
Order By: Relevance
“…To study the association between IL-1β expression and AGF diversity, we performed a correlation analysis. Our previous studies have reported that a decrease in synaptic plasticity marker BDNF played a key role in brain pathology in GW chemical exposed mice [44] Results showed that expression of BDNF significantly decreased (p=<0.00001 between Control vs GWI & GWI vs GWI_FMT) in GWI group when compared to Control and GW_FMT mice groups (Fig 6d). Interestingly, a negative correlation (r=-0.8866, p=0.19 & r=-0.9799, p<0.001) was observed between BDNF and AGFs suggesting that increased AGF-α-diversity may have a strong influence on observed neuroinflammation GWI mice group (Fig 6j)…”
Section: Gastrointestinal Systemic and Neuronal Inflammation And Its Association With Args And Drug Classes In Mouse Gw-cmi Samplesmentioning
confidence: 69%
See 1 more Smart Citation
“…To study the association between IL-1β expression and AGF diversity, we performed a correlation analysis. Our previous studies have reported that a decrease in synaptic plasticity marker BDNF played a key role in brain pathology in GW chemical exposed mice [44] Results showed that expression of BDNF significantly decreased (p=<0.00001 between Control vs GWI & GWI vs GWI_FMT) in GWI group when compared to Control and GW_FMT mice groups (Fig 6d). Interestingly, a negative correlation (r=-0.8866, p=0.19 & r=-0.9799, p<0.001) was observed between BDNF and AGFs suggesting that increased AGF-α-diversity may have a strong influence on observed neuroinflammation GWI mice group (Fig 6j)…”
Section: Gastrointestinal Systemic and Neuronal Inflammation And Its Association With Args And Drug Classes In Mouse Gw-cmi Samplesmentioning
confidence: 69%
“…The fixed mouse small intestine and frontal cortex tissues were paraffin embedded and 5 µm thick sections were done for immunohistochemistry. Deparaffinization were performed following previous protocol [44]. Antigen retrieval was performed using epitope retrieval solution and steamer (IHC world, Woodstock, MD, USA).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Tight junction (TJ) proteins are responsible for maintaining epithelial barrier integrity, which in turn is essential for regulating nutrient absorption, transport of selective content from the lumen, and blockage of pathogen entry [ 38 , 39 ]. In our previous studies, we showed that GW chemical exposure led to an altered expression of TJ proteins, where Claudin-2 expression was increased with a simultaneous decrease in Occludin expression, leading to gut leaching [ 7 , 11 ]. In this study, we wanted to show whether AG was able to revert the altered expression of TJ proteins in GW chemical-exposed mice.…”
Section: Resultsmentioning
confidence: 99%
“…GW chemicals (PER and PB) were used to expose the mice following well-established acute rodent models of Gulf War illness with some modifications [ 7 , 9 , 11 ]. All mice were randomly divided into 4 groups after 1 week of acclimatization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation